PENGARUH HARI RAYA IDUL ADHA TERHADAP PERMINTAAN IKAN AIR TAWAR KONSUMSI DI MASYARAKAT - Wibowo, Tri Adi; Untari, Desy Sasri; Emilyasari, Desi (Universitas Pattimura, 2024)
Indonesia as a country with a majority Muslim population has several celebrations of religious holidays. One of these religious holidays is Eid al-Adha. On this holiday, a ritual is carried out, namely the slaughter of animals such as cows or goats, which later the meat from the slaughter will be distributed to people in need. Recipients of Eid al-Adha sacrificial meat that touch all levels of society, will certainly affect the purchasing power of food sources of animal protein in the market such as fish. Consumption of red meat derived from sacrificial meat will affect the purchase of freshwater fish. The results showed a decrease in the number of fish stocks sold by traders and low public interest in buying fish since seven days before the implementation of Eid al-Adha. Meanwhile, a day to three days after Eid al-Adha, there has not been any freshwater fish consumption trading activity in the market. Trading activities began to run normally on the fourth day, accompanied by an increase in the price of fish sold by traders in the range of 10% to 15% compared to normal days. This price increase is caused by increased demand by consumers to buy fish, which is caused by consumers experiencing boredom with all-round menu dishes of red meat that they though of sacrificial meat. Keywords: Eid Al-Adha, Sacrificial Meat, Freshwater Fish